Structure, reactions, and partial syntheses of indole derivatives / Low Yun Yee - Low, Yun Yee (2013)

(untitled)
Two new alkaloids of the mersinine type, mersiphyllines A (37) and B (38), were isolated from the polar fraction of the alkaloid extract of K. singapurensis following repeated fractionation via gel-permeation chromatography. The structures of these alkaloids were elucidated based on NMR spectroscopy, formation of an alkaloid-borane complex 40, as well as X-ray diffraction analysis. Concise partial syntheses of several new indole alkaloids isolated from Tabernaemontana, Alstonia, and Leuconotis species were carried out. These include, lirofoline A (44) from ibogaine (46), alstolucine A (91) from alstolucine B (94), and ()-eburnamaline (96) from (+)-eburnamonine (98). Some transformations of the ring-opened Aspidosperma alkaloid, leuconolam (54) were investigated, inter alia, its reactions with base leading to enolate-mediated ring closure to yield the epimeric pentacylic meloscine-like compounds (74 and 76), its reaction with acids leading to transannular closure to the pentacyclic, doubly spirocyclic, 6,7-dehydroleuconoxine (63), or to the tetracyclic amino lactam-lactone (78). Bromination (Br2/CHCl3) of leuconolam (54) was shown to proceed via a two-step sequence involving the intermediacy of 6,7-dehydroleuconoxine (63). Other reactions investigated include enolate-mediated -oxygenation, hydroboration, and reaction with trifluoroacetic acid. These studies led to concise semisynthesis of leuconoxine (56), and the new leuconoxine alkaloids, leuconodines A (67) and F (72). The results from these reactions also led to the realization that the original assignment of epi-leuconolam as 55 was incorrect. This was confirmed upon carrying out an X-ray diffraction analysis, which showed that ‘epi-leuconolam (55)’ is in actual fact 6,7-dehydroleuconoxine (63). The original stereochemical/configurational assignments of the alkaloids scholaricine (114a) and alstoumerine (118a) were reinvestigated (NMR, derivatization, iii X-ray diffraction analysis) and the structures revised accordingly (to 114b and 118b, respectively). The revised structure of alstoumerine (118b) was necessary for the structure elucidation of the new bisindole, lumutinine C (116). X-ray diffraction analyses were carried out for the macroline-macroline bisindole alkaloids, perhentinine (104) (via formation of the dimethyl diiodide salt of the ring E-cyclized hemiketal form, 104b) and macralstonine (105), and the results were then applied to support the configurational assignment of C-20 in the new Alstonia bisindoles, perhentidines AC (101103). Andransinine (119) (in all probability an artifact derived from the alkaloid andranginine (120) during isolation of alkaloids from A. angustiloba and K. pauciflora), was found to exhibit polymorphism in the solid state, forming crystals with different crystal systems and space groups in different solvent systems. In addition, it undergoes spontaneous resolution when crystallized in ethyl acetate, forming racemic conglomerate crystals. X-ray diffraction analyses of a number of new indole and bisindole alkaloids isolated from various plants of the genus Alstonia, Kopsia, Leuconotis, and Tabernaemontana were carried out. These include: the bisindole alkaloids, leuconoline (124) from L. griffithii, and lumusidines A (125) and B (126) (via its dimethyl diiodide salts, 125a and 126a) from A. macrophylla, the novel indole alkaloids voatinggine (128) and tabertinggine (129) from T. corymbosa, grandilodines A (135) and B (136) from K. grandifolia, and leuconodines B (68) and E (71) from L. griffithii.